Swallow–Breath Interaction and Phase of Respiration with Swallow during Non-Nutritive Suck in Infants Affected by Neonatal Abstinence Syndrome - Reynolds, Eric W.; Grider, Debbie; Bell, Cynthia S. (Frontiers in Pediatrics, 2017)
Background The development of suck–swallow–breath rhythms during non-nutritive suck (NNS) may be an indicator of neurologic integrity. We have described swallow–breath (SwBr) interaction and phase of respiration (POR) with swallow during NNS in low-risk preterm (LRP) infants. NNS in infants with neonatal abstinence syndrome (NAS) has not been described with our method. Method Suckle, swallow, thoracic motion, and nasal airflow were measured during NNS in 10 infants with NAS and 12 unaffected infants (control). Logistic regression models were fit to describe the three types of SwBr and five types of POR in terms of the independent variables (gender, gestational age, birth weight, postmenstrual age, weeks postfirst nipple feed and swallows per study). We also compared the NAS group to 16 LRP infants. Results In the NAS group, there were 94 swallows in 18 studies. In the control group, there were 94 swallows in 12 studies. There were statistical differences between groups for all three types of SwBr. The distribution of SwBr in NAS was similar to LRP infants with NAS having fewer swallows with attenuated respiration and more with central apnea. For POR, there were few differences. Over time, the distribution of SwBr in NAS infants approaches that of control infants. Discussion Variability in SwBr and POR during NNS may represent neurologic dysfunction in infants with NAS. Specifically, term infants with NAS display an immature pattern of SwBr making them more similar to preterm infants, rather than a unique pathology. The distribution of SwBr and POR in NAS infants becomes more like term infants, possibly representing catch-up development as the NAS symptoms resolve. Conclusion SwBr in babies with NAS is different from that of unaffected term infants, actually being similar to preterm infants. Infants with NAS exhibit a dysmature pattern of NNS development which resolves over time.